2007
DOI: 10.1007/s11926-007-0074-2
|View full text |Cite
|
Sign up to set email alerts
|

Axial disease in psoriatic arthritis

Abstract: The definition of axial disease in psoriatic arthritis has varied from isolated unilateral grade 2 sacroiliitis to criteria similar to those used for ankylosing spondylitis. Depending on the definition used, the prevalence of axial disease varies from 25% to 70% of patients with psoriatic arthritis. This article reviews the prevalence, clinical and radiologic features, pathogenesis, prognosis, and treatment of psoriatic spondylitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
1
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(77 citation statements)
references
References 27 publications
2
66
1
8
Order By: Relevance
“…Moreover, to support the assumptions that an equivalency between axial PsA and AS may not hold up, previous studies showed that the Bath Ankylosing Spondylitis Disease Activity score (BASDAI) in PsA was significantly lower than AS, correlated poorly with external indicators of disease activity [15] and may be influenced by the peripheral involvement, showing again the difference between these two conditions [16]. All these interesting data confirmed, to some extent, that axial PsA is quite different to the classical AS and is usually less severe [17].…”
Section: Introductionmentioning
confidence: 72%
“…Moreover, to support the assumptions that an equivalency between axial PsA and AS may not hold up, previous studies showed that the Bath Ankylosing Spondylitis Disease Activity score (BASDAI) in PsA was significantly lower than AS, correlated poorly with external indicators of disease activity [15] and may be influenced by the peripheral involvement, showing again the difference between these two conditions [16]. All these interesting data confirmed, to some extent, that axial PsA is quite different to the classical AS and is usually less severe [17].…”
Section: Introductionmentioning
confidence: 72%
“…A number of the radiographic features of AxPsA are similar to those found in ankylosing spondylitis (AS), although patients with AS generally have more severe radiographic damage compared to AxPsA (5). For example, the sacroiliitis seen in AxPsA may be difficult to distinguish radiographically from that found in AS, and may be milder clinically (2,5). PsA patients also have new bone formation that resembles the syndesmophytes seen in AS patients.…”
Section: Introductionmentioning
confidence: 92%
“…Involvement of the axial joints, termed axial PsA (AxPsA), is relatively common and ties PsA to the concept of spondyloarthritis (SpA). Due to differences in the criteria used for defining AxPsA, there is wide variability (25-70%) in the reported prevalence of axial involvement in PsA (2). AxPsA can affect the sacroiliac (SI) joints, as well as the lumbar, thoracic, and cervical spine (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Axial PsA has been defined in many ways, varying from an isolated unilateral grade 2 sacroiliitis to those criteria used for Ankylosing Spondylitis (AS) (32)(33). Therefore, the prevalence of this subset of patients, depending on disease stage and criteria used, is very broad ranging A C C E P T E D M A N U S C R I P T…”
Section: Definition Of Axial Psamentioning
confidence: 99%